Analisis Nilai Islami Terhadap Lingkungan Internal Pondok Pesantren Tahfidz Darul Furqon Blu’uran - Sukron, Sukron; Fajariyah, Nurul (El-Idare: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to analyze the internalization of Islamic values ​​within the internal environment of the Darul Furqon Blu'uran Tahfidz Islamic Boarding School. The focus of the study is directed at the implementation of Islamic values ​​integrated into the education system, the habituation of religious behavior, and social relations among Islamic boarding school residents. The research method used is descriptive qualitative with data collection techniques through observation, in-depth interviews, and documentation. The data obtained are analyzed using data reduction techniques, data presentation, and conclusion drawing. The results of the study indicate that Islamic values ​​are internalized through three main approaches, namely exemplary behavior from educators, the habituation of worship in daily routines, and the strengthening of Islamic boarding school culture that is inspired by the values ​​of the Qur'an. The leadership of the kiai plays a central role in shaping the character of students through intensive supervision, the application of discipline, and the fostering of a sense of collective responsibility. This contributes to the creation of a religious and harmonious educational environment that supports the development of students' character as memorizers of the Quran with noble morals. This research confirms that optimizing the internal environment of Islamic boarding schools is a key factor in strengthening the comprehensive internalization of Islamic values. Therefore, strengthening Islamic boarding school management is necessary to maintain the consistent application of Islamic values ​​relevant to the needs of today's developments.